Enhanced sulfate formation by nitrogen dioxide: Implications from in situ observations at the SORPES station. Issue 24 (17th December 2015) - Xie, Yuning; Ding, Aijun; Nie, Wei; Mao, Huiting; Qi, Ximeng; Huang, Xin; Xu, Zheng; Kerminen, Veli‐Matti; Petäjä, Tuukka; Chi, Xuguang; Virkkula, Aki; Boy, Michael; et al.
Abstract: Investigating sulfate formation processes is important not only for air pollution control but also for understanding the climate system. Although the mechanisms of secondary sulfate production have been widely studied, in situ observational evidence implicating an important role of NO2 in SO2 oxidation in the real atmosphere has been rare. In this study, we report two unique cases, from an intensive campaign conducted at the Station for Observing Regional Processes of the Earth System (SORPES) in East China, showing distinctly different mechanisms of sulfate formation by NO2 and related nitrogen chemistry. The first case occurred in an episode of mineral dust mixed with anthropogenic pollutants and especially high concentrations of NO x . It reveals that NO2 played an important role, not only in surface catalytic reactions of SO2 but also in dust‐induced photochemical heterogeneous reactions of NO2, which produced additional sources of OH radicals to promote new particle formation and growth. The second case was caused by aqueous oxidation of S(IV) by NO2 under foggy/cloudy conditions with high NH3 concentration. As a by‐product, the formed nitrite enhanced HONO formation and further promoted the gas‐phase formation of sulfate in the downwind area. This study highlights the effect of NO x in enhancing the atmospheric oxidizing capacity and indicates a potentially very important impact of increasing NO x on particulate pollution formation and regional climate change in East Asia. Key Points: Enhanced sulfate formation in dust and biomass burning plumes Heterogeneous photochemical reactions promoted sulfate formation on dust Aqueous‐phase formation of sulfate by NO2 in mixed plumes